Infrared thermography-based condition monitoring of solar photovoltaic systems: A mini review of recent advances. (15th July 2021) - Kandeal, A.W.; Elkadeem, M.R.; Kumar Thakur, Amrit; Abdelaziz, Gamal B.; Sathyamurthy, Ravishankar; Kabeel, A.E.; Yang, Nuo; Sharshir, Swellam W.
Highlights: An overview for infrared thermography (IRTG) detection of PVs is introduced. Classification of IRTG techniques, detected faults are discussed in detail. The manuscript provides a good guide for selecting a proper IRTG system for PV plants. Abstract: Globally, solar photovoltaic (PV) plants have been in continuous increase, attracting researchers and governments' interest, and PV markets witness high competition. That requires advanced research and development of reliability and efficiency optimization, fault detection and diagnosis, and maintenance of various components, particularly PV modules. Along with that, many works and technical investigations have been conducted via many detection methods based on either indoor or outdoor tests. Specifically, the temperature is a common indicator of any structure components' health as faulty and damaged components, and corroded electrical connections can lead to abnormal temperature distribution. Hence, such faults can be detected through imaging and analyzing temperature distribution patterns localizing the faulty part. For so, Infrared Thermography (IRTG) has become a widely-utilized condition monitoring (CM) technique; through which real-time temperature can be measured. It is regarded as reliable, accurate, and economical method due to the advent of IR cameras. IRTG features for being safe and non-destructive testing technique (NDTT); and hence it has been effectively used in detecting PV plants either in small or large scales. This survey manuscript presents a general view about IRTG and focuses on its utilization in condition monitoring of PV plants merging the state-of-the-art researchers' efforts in this field. In addition, some common patterns of detected faults and their analyses are also illustrated.